ENHANCING READING LITERACY THROUGH TECHNOLOGY INTEGRATION (International conference on multidisciplinary science, 2024)
Integration is considered one of the most relevant topics of today's world. Achieving effectiveness in education through technology integration is possible. This article provides the content and essence of enhancing reading literacy through technology integration.